Hematology of the bronze Turkey (Meleagris gallopavo): Variations with age and gender - Schmidt, Elizabeth Moreira dos Santos [UNESP]; Paulillo, Antonio Carlos [UNESP]; Martins, Gislaine Regina Vieira [UNESP]; Lapera, Ivan Moura [UNESP]; Testi, Alan Jonathan Pereira [UNESP]; Nardi Junior, Leonildo [UNESP]; Denadai, Janine [UNESP]; Fagliari, José Jurandir [UNESP] (My University, 2009)
One hundred and ten Bronze Turkeys: 40 females (19-23 week-old), 13 males (19-23 week-old), 35 females (30-32 week-old) and 22 males (30-32 week-old), were investigated to analyse the influences of age and sex on hematological parameters. Statistical comparisons were made for differences in values between male and female and among different ages. Lymphocytes were the major circulating leukocyte for all birds. Total serum protein, lymphocytes and basophils were significantly different between females of both ages. The RBC values were significantly different between males of both ages. © Asian Network for Scientific Iformation, 2009.
Keywords: Avin hematology; Bronze turkeys; Meleagris gallopavo; Total plasma protein; Aves